Benefits of Participation in Student Organization in Tourism Education: Professional and Working Opportunities Through Experience - Ningrum, Lestari; Azalia, Monica (Institut Pariwisata Trisakti, 2018)
Extracurricular organizations are beneficial to college students. They help in bringing students and institutions together, let students interact in a non-formal atmosphere, and allow students to strengthen their leadership and communication skills. There are at least what books, articles, and advisors will tell the students. In today’s society, employers are hiring students more on what they can do, not their grade point average. Participating in extracurricular organizations shows future employers that students can handle school, work, and other activities, which in turn shows responsibility and organization. Do students really understand this?. Sometimes labeled as